PENGARUH LIKUIDITAS DAN KEPEMILIKAN PUBLIK TERHADAP KETEPATAN PENYAMPAIAN LAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI DI INDEKS SAHAM SYARIAH INDONESIA - Muhammad Al Fajri; Mohammad Orinaldi; Nurrahma Sari Putri (Jurnal Riset Manajemen dan Akuntansi, 2023)
This research was conducted with the aim of examining the effect of liquidity and public ownership on the timely submission of financial reports to companies in the consumer goods sector in the Sharia Stock Index for 2019-2022. This study was tested using 2 independent variables, namely: liquidity and public ownership. The dependent variable (dipendent) is the timeliness of submission of financial reports. The samples used in this study were 84 samples. The analysis of this research is logistic regression analysis and assisted by Eviews analysis 12 data used is panel data. The results of this study are that liquidity and public ownership partially have no significant effect on the timeliness of submission of financial reports. The results of the simultaneous test of liquidity and public ownership have an influence on the timeliness of submission of financial reports.